2018
DOI: 10.4258/hir.2018.24.4.283
|View full text |Cite|
|
Sign up to set email alerts
|

Need Assessment for Smartphone-Based Cardiac Telerehabilitation

Abstract: ObjectivesTo identify the current status of smartphone usage and to describe the needs for smartphone-based cardiac telerehabilitation of cardiac patients.MethodsIn 2016, a questionnaire survey was conducted in a supervised ambulatory cardiac rehabilitation (CR) program in a university affiliated hospital with the participation of heart failure or heart transplantation patients who were smartphone users. The questionnaire included questions regarding smartphone usage, demands for smartphone-based disease educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Third, unlike other studies [ 36 , 60 ], we did not collect patients’ HF clinical characteristics (eg, New York Heart Association Class or left ventricular ejection fraction) to explore potential relationships between HF severity and smartphone adoption or use. A similar study found that these characteristics were not associated with the adoption or perceptions of mHealth [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, unlike other studies [ 36 , 60 ], we did not collect patients’ HF clinical characteristics (eg, New York Heart Association Class or left ventricular ejection fraction) to explore potential relationships between HF severity and smartphone adoption or use. A similar study found that these characteristics were not associated with the adoption or perceptions of mHealth [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that this imbalance did not affect our study results, as previous studies have shown that there are no significant differences in smartphone and mHealth adoption between men and women [34,46]. Third, unlike other studies [36,60], we did not collect patients' HF clinical characteristics (eg, New York Heart Association Class or left ventricular ejection fraction) to explore potential relationships between HF severity and smartphone adoption or use. A similar study found that these characteristics were not associated with the adoption or perceptions of mHealth [36].…”
Section: Limitationsmentioning
confidence: 96%
“…The medical fees for CR are usually covered by the national health system, and this poses a realistic barrier in that the demand and profit may not be high enough to operate CR centers. Contrary to this reality, patients with HF in South Korea show high usage of internet and interest in mobile health technology, 66) and smartphone-based cardiac telerehabilitation programs are expected to develop in high-demand areas. As the telemonitoring method using wearable devices has been recently approved for insurance coverage in Korea, it is expected that telerehabilitation programs using such medical devices will also be widely performed in the near future.…”
Section: Possible Barriers To Cr In Hfmentioning
confidence: 99%